Implications of socio-demographic change in place of death in Scotland 2001-2011: an analysis of linked census and death registration data - Atherton, Iain; Schneider, Anna (International Journal of Population Data Science, 2019)
Background with rationale Care in the final stages of life care constitutes a marked component of all health and social care expenditure. Whether people die at home or in an institutional setting is influenced by a range of social and demographic factors. Understanding the implications of socio-demographic trends for people die can contribute to planning services. Main Aim To describe changes in place of death 2001-2011 and to ascertain the extent to which these might be explained by social or demographic trends. Methods/Approach Data from the Care in the Last Days of Life Study was drawn on. This dataset linked census to death registration and hospital admissions data for all deaths occurring in the 12 months following the 2001 and 2011 censuses. Deaths in these two time periods were compared and contrasted using logistic regression. Results and Discussion Excluding deaths for which no census record could be linked, a total of 56,766 people died in the year following the 2001 census and 53,517 following in the same period after the 2011 census. A slight decline was apparent in the period proportion of deaths in hospital (52.3% of all deaths in 2011-12 against 56.9% in 2001-02) with a concomitant increase in deaths in care homes and hospices. Deaths at home were virtually unchanged. Age at death increased markedly with 31.4% occurring to people aged 85+ years in the latter compared to 26.6% in the earlier period. Further analysis to be presented will explore the extent to which these changes can be explained by an ageing population, shifting causes of death, changes in hospital discharge policies, or social composition of the Scottish population between these two timepoints. Implications of findings for policy will be considered.